Analisis Pengendalian Kualitas Produk Part Arm Rear Brake KWBF Dengan Metode Six Sigma (DMAIC) - One Azalea Muchammad; Apid Hapid Maksum; Muhamad Taufiq Rachmat (Fakultas Teknik, 2023)
PT. CKA is a private industry engaged in the production of metal stamping parts, tools, and dies. In making this product, we used the concept of production based on orders. In the manufacturing process, operator performance is considered less than optimal due to waste. These products require high accuracy and a fixed duration so that the process does not produce defective or unfavorable products. PT. CKA is committed to maintaining product quality through consistent manufacturing practices. In practice, the Kwbf Arm Rear Brake Part is the product that most often shows manufacturing defects. The application of this research connects various activities, such as identifying factors that cause product damage and then analyzing the causes of product damage using Lean Six Sigma. This study intends to analyze the factors that cause defects using the Six Sigma approach with the DMAIC concept, then, through fishbone diagram analysis and 5W+1H, make a proposal based on the stabilized type. Implementation suggestions resulted in SOP adjustments, work systems, and additional tools. The results of the study show that the DPMO value is 5674, which means that for one million there is a possibility of 6190.75 possible defects in the product produced. Kwbf's Arm Rear Brake Part products have a sigma level of 4.03, with the highest percentage of defects found in Blunt Serration (32%), Spot Welding Points Not Centered (30%), and Scratch Materials (26%). After analysis, it can be concluded that the causes of defects are human factors, methods, machines, the environment, and tools.